A New Method of Predicting the Distribution of Remaining Oil by the Composite Index of Heterogeneity. (July 2020) - Gao, Ang
Abstract: As the Xingbei Development Zone gradually goes into the extra high water cut stage, the difficulty of residual oil tapping is becoming harder and harder. Heterogeneity not only controls the injection agent's sweep coefficient, but also controls the injection displacement efficiency, which is the key factor affecting the formation and distribution of residual oil. Characterization of reservoir macroscopic heterogeneity by parameters such as sedimentary microfacies, oil layer structure, permeability, porosity and net thickness ratio. The heterogeneous comprehensive index obtained by the wave superposition method can not only quantitatively evaluate reservoir heterogeneity, but also explain the distribution characteristics of the residual oil. Using this method to fit the eastern part of a district of Xingbei Oilfield, The obtained heterogeneous composite index (IRH) distribution map is compared with the reservoir numerical simulation residual oil saturation map, and the correlation between the two is good. Statistically fit the production of new wells in the simulated area, wells with heterogeneous composite index between 0.55 and 0.75 have higher cumulative oil production, average daily oil production, and the water content is 2-5 percent lower than the average. According to the comprehensive analysis, the remaining oil enrichment area is in the IRH [0.55, 0.75] region. Guided by this method, we repart Well B1; let free its S II 8 accompanying water blocking layer, so as to strengthen liquid supply to Well B2 and Well B3, which are rich in residual oil through this method. The production plan proves to be effective, Well B2's daily oil production increases by 1.5t, and Well B3's daily oil production increases by 1.2t. Till now, the accumulated increasing oil production has up to 1324t, which equals to economic benefits of 3840, 000 RMB. Through quantitative characterization of reservoir heterogeneity, we find that the remaining oil enrichment zone is mostly located in the IRH [0.55, 0.75] region, which has important guiding significance for the future development.